ANALISIS SUMBER DAN PENGGUNAAN MODAL KERJA UNTUK MENGUKUR KINERJA KEUANGAN PADA PT.TIMAH (persero) Tbk (PENGAMATAN DI BEI PERIODE TAHUN 2009-2012) - Prayogo, Tony Setyo; Maqsudi, Achmad (JEA17: Jurnal Ekonomi Akuntansi, 2016)
Working capital is an important element for any company because without sufficient working capital, operational activities of a company can not be held. Along with the rapid growing of business recently, as well as the intensive increasing competition, obtaining an adequate working capital has become a major factor to be considered. The amount of working capital required by each company is not the same and can not be determined by any standard. Lack of working capital will continually hamper business activities and thus companies productivity will not run well, otherwise the excess of working capital will lead to unproductive funds which will cause in a loosing gain or profits. This study used an object of PT.Timah (Persero) Tbk. for year of 2009-2012 observed data. It was using analyzing technique of raising and using of working capital. It showed that in the year 2009-2010 the use of the net working capital had excess of Rp 769 323, In the year 2010-2011 had excess of Rp. 323.320. Otherwise, in 2001-2012 the company's net working capital showed deficit of Rp.192.870. From the results of this analysis, it can be concluded that the net working capital of the company was not effectively managed in the year of 2009 to 2012. The decreasing in net working capital was due to the inceasing of non-current assets purchased by long-term debt and owner’s equity. Decreasing in net working capital will lead to a shortage in the company's operating expenditure. We recommend that the company must protect against the crisis of working capital and it must pay all obligations in a timely manner in order to increase the net working capital. The company should avoid experiencing a shortage of working capital since the availability of working capital is a vital instrumental to assist any companies in financing all daily operational activities. In addition the company's goals can be achieved and good progress can be maintained by keeping an adequate and proper level of working capital.Keywords: Working Capital, Financial Performance